Pediatric keloids: a 6-year retrospective review (2017)
Background/Objectives: Keloids are reportedly rare at the extremes of life. We sought to describe the epidemiology of pediatric keloids seen at the plastic surgery outpatient department of the University College Hospital, Ibadan. Methods: We retrospectively reviewed all children younger than 19 years who presented with nonburn keloids between 2008 and 2014. Data were obtained on age; duration, size, and location of the keloid; family history; mode of treatment; and outcome. Outcome variables were recurrence and wound complications. Data were analyzed using the Pearson chi-square test for discreet variables and the independent- sample t test for continuous variables. P < .05 was taken as statistically significant. Results: Within the review period, 304 patients presented with keloids, of whom 40 (13.1%) were younger than 19 years. There was a female preponderance (n = 23, 57.5%). The mean age at onset of the keloid was 9.3 years (range 3 months-18 years). Thirty (75%) patients had keloids in the head and neck region. Keloids were sporadic in 31 (77.5%) patients. Nineteen (47.5%) patients had multimodal treatment for keloid. The recurrence rate was 20%. Recurrence was significantly associated with the size of the lesion (P = .003). Conclusion: Keloids during childhood are not rare. More attention should be paid to the management of keloids in this age group.